Healthcare Workers’ Emotions, Stressor Experiences and Coping Strategies During the COVID-19 Pandemic in Vietnam - Thai TT; Nguyen TH; Pham PTT; Bui HHT; Bui TNM (Dove Medical Press, 2021)
Truc Thanh Thai,1 Thinh Huu Nguyen,2 Phuong Thu Thi Pham,3 Han Hy Thi Bui,4 Tam Ngoc Minh Bui2 1Faculty of Public Health, University of Medicine and Pharmacy at Ho Chi Minh City, Ho Chi Minh City, Vietnam; 2Training and Scientific Research Department, University Medical Center Ho Chi Minh City, Ho Chi Minh City, Vietnam; 3Hospital for Rehabilitation - Occupational Diseases at Ho Chi Minh City, Ho Chi Minh City, Vietnam; 4Woolcock Institute of Medical Research, Hanoi, VietnamCorrespondence: Truc Thanh ThaiFaculty of Public Health, University of Medicine and Pharmacy at Ho Chi Minh City, Ho Chi Minh City, VietnamTel +84 908 381 266Email thaithanhtruc@ump.edu.vnTam Ngoc Minh BuiTraining and Scientific Research Department, University Medical Center Ho Chi Minh City, Ho Chi Minh City, VietnamTel +84 906 951 668Email tam.bnm@umc.edu.vnPurpose: Healthcare workers (HCWs) are a crucial resource in the battle against the COVID-19 pandemic but are vulnerable to both SARS-CoV-2 infection and negative psychological consequences. This study evaluated HCWs' emotions, stressor experiences and coping strategies during the pandemic.Methods: A cross-sectional study was conducted among HCWs at the University Medical Center in Ho Chi Minh City. The questionnaire was adapted from the MERS-CoV Staff Questionnaire to measure HCWs' emotions, stressor experiences and coping strategies during the COVID-19 pandemic.Results: Among the 1423 participants eligible in the data analysis, the majority were female (71.1%) with a mean age of 34.2 (standard deviation 7.8) years. While most participants reported that they did their job because of their professionalism and duty as HCWs (87.4%), a high number reported feeling nervous and scared (86.0%). Most participants reported worry about transmitting SARS-CoV-2 to their families or friends (76.6%) and concern that a small mistake or lapse in concentration could infect themselves and others (76.7%). The most common coping strategies were following strict personal protective measures (95.3%), avoiding going out (92.5%) and reading about SARS-CoV-2 (92.3%). Females who had a higher educational level and less than 5-years work experience and those who worked at clinical departments and subclinical departments were more vulnerable.Conclusion: This study indicates an urgent need for psychological support for HCWs, especially for those at high risk of having stress. Interventions and support should utilize psychological resources and approaches effectively to adapt to the new situation during the COVID-19 pandemic.Keywords: stressor experience, coping strategy, motivational factors, health care worker, COVID-19